1995
DOI: 10.1063/1.115258
|View full text |Cite
|
Sign up to set email alerts
|

Growth and giant magnetoresistance properties of La-deficient LaxMnO3−δ (0.67≤x≤1) films

Abstract: Epitaxial thin films of lanthanum-deficient LaxMnO3−δ (0.67≤x≤1) have been grown on (100) SrTiO3 substrates by pulsed laser deposition. The as-deposited films exhibit a ferromagnetic transition at temperatures ranging from 115 to 240 K, with the transition temperature (Tc) increasing with higher La deficiency. A sharp drop in resistivity and negative magnetoresistance is observed close to Tc, a behavior similar to that observed in divalent substituted La1−xMxMnO3−δ (M=Ba, Sr, Ca, Pb) films. Postannealing the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
87
1
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(108 citation statements)
references
References 0 publications
12
87
1
1
Order By: Relevance
“…The unexpected ferromagnetism was considered to be extrinsic and deficiency of La [10,14] was suggested as a possible explanation to it. However, it is not consistent with the fact that FM phase in the LMO thin films with cation deficiency tends to be metallic [7,15,16]. Previous models [17,18] and recent first-principles studies [19,20] on LMO thin films predicted the metallic FM phase, instead of the experimentally observed insulating FM phase.…”
contrasting
confidence: 41%
See 2 more Smart Citations
“…The unexpected ferromagnetism was considered to be extrinsic and deficiency of La [10,14] was suggested as a possible explanation to it. However, it is not consistent with the fact that FM phase in the LMO thin films with cation deficiency tends to be metallic [7,15,16]. Previous models [17,18] and recent first-principles studies [19,20] on LMO thin films predicted the metallic FM phase, instead of the experimentally observed insulating FM phase.…”
contrasting
confidence: 41%
“…Since the Based on the established orbital order, the magnetic interactions among the Mn atoms in the insulating P21/n FM phase can be deduced according to the Goodenough-Kanamori rules [21]. As a result of the three-dimensionally , higher than experimentally measured ones [7,11] ranging from 115K to 240K. A possible explanation to this discrepancy is that the epitaxial strain is gradually relaxed from the substrate to the film surface, thus the FM phase locates just near the strained film-substrate interface while the bulk-like A-AFM phase dominates at the film surface, similar to the case of the strain-induced ferromagnetism in the antiferromagnetic LuMnO 3 thin film [35].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We feel that one of the possibilities for a higher T p and T c for xϭ0. 2 8 It has been shown that T c of the as-deposited thin film sample of La 0.75 MnO 3 has increased from ϳ240 to ϳ300 K after annealing in oxygen and the resistivity of La 1Ϫx MnO 3 decreases with increasing x. Therefore, the high T c and T p and the lower resistivity of the thin film sample, 1 compared to that of the bulk, are in accordance with the La deficiency of the film.…”
Section: ͓S0003-6951͑00͒02409-8͔supporting
confidence: 49%
“…A magnetoresistance of 85% under 6T was obtained in La 0.7 MnO 3 films on LaAlO 3 prepared by pulsed laser deposition (PLD) with a substrate temperature of 993K [7]. Gupta et al [8] reported a magnetoresistance of 55% under 4T in La 0.75 MnO 3 films grown by PLD on SrTiO 3 at 973K.…”
Section: Introductionmentioning
confidence: 99%